Design of Educational Tourism Management (Eduwisata) Model of Kampung Inggris - Laksono, Sonny Subroto Maheri (Prosiding Seminar; 2020: 2020 International Conference of Interdisciplinary Sciences, 2020)
Kampung Inggris is an area located in Pelem and Tulungrejo Villages, Pare District, Kediri Regency. This research is aimed at designing an educational tourism management model that is suitable with the conditions and conditions in Kampung Inggris tourism destinations. This type of research is descriptive with a qualitative approach. Data is collected through observation, interviews and documentation studies. Educational tourism is a tourism management concept that combines tourism activities with educational activities. The results showed that the purpose of this concept is for tourists to get direct learning in attractions, in this case that is understanding and mastery of foreign languages, especially English properly and correctly, and understanding of the culture of the community and the local wisdom of the Pare and surrounding communities. Tourism management essentially involves the role of all existing stakeholders. There are several stakeholders involved, namely: Government, Community and Private. In this research a community-based educational tourism management (CBT) management model has been developed.